Alternatif-Alternatif Langkah Dinas Kesehatan Meningkatkan Keterlibatan Pegawai Puskesmas Dalam Aplikasi Sistem Informasi Manajemen Puskesmas (Studi Kasus Di Dinas Kesehatan Kabupaten Brebes, Jawa Tengah) - Uswatun Nisaa (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2010)
One of the factors causing ineffective puskesmas management information system (simpus) application is the low puskesmas employee involvement. The purposes of the research are identifying causal factors of the low employee involvement from individual and organizational factors, and analyzing alternatives of step of Brebes District Health Department (DKK Brebes) to enhance puskesmas employee involvement. The research objects were DKK Brebes and 4 of its UPT (2 good employee involvement puskesmas, and 2 low employee involvement puskesmas). The individual factors research subjects were all puskesmas employees involved voluntarily and mandatorily in simpus application (8 employees in good employee involvement puskesmas, and 6 in low employee involvement puskesmas). The organizational factors research subjects were the Chief of Program Development and Health Resources of DKK Brebes, a professional staff of Information Management and Health Program Development section, a simpus staff in Jatibarang Puskesmas, and a simpus coordinator in Brebes Puskesmas.  Data was collected by deep interview, questioner, and observation.  The data analysis techniques were descriptive statistic and non statistic analysis. The research showed that the main individual factors causing the low employee involvement were the limited knowledge and skill of puskesmas employees. Based on organizational factors (DKK Brebes and puskesmas), the causal factors were simpus management, change management, and learning organization development that were not optimum.  Alternatives of step of DKK Brebes to enhance puskesmas employee involvement in simpus application: (1) building better simpus management; (2) creating change management based on puskesmas condition; and (3) developing better learning organization in puskesmas.